The Effects of Using an Interactive Software (GSP) on UAE Students’ Attitudes towards Geometry - Almeqdadi, Farouq (American Journal of Social Sciences and Humanities, 2018)
This study investigated the effects of using the Geometer’s Sketchpad (GSP) software on the UAE math teachers’ and students’ Attitudes towards Geometry. The sample consisted of 8 math teachers and 98 students (males and females) in grade 9 from Al-Ain Educational Zone in UAE. The researcher trained the teachers in the study on the use of GSP. After that, the teachers, in turn, trained the students on the use of the software. The participants completed an attitude questionnaire pre- and post- use of the software. The results of the study showed significant differences in students’ attitudes towards geometry. They showed more positive attitudes after using the GSP than before using it in geometry classes. The results also revealed that most of the 9th grade students in the experimental had positive attitudes towards geometry.